2014
DOI: 10.1007/s00520-014-2513-8
|View full text |Cite
|
Sign up to set email alerts
|

Trajectories of fear of recurrence in women with breast cancer

Abstract: Purpose Although fear of recurrence (FCR) is common among cancer survivors, it remains unclear what factors predict initial levels (e.g., prior to surgery) or changes in FCR in the post-treatment period. Among women treated for breast cancer, this study evaluated the effects of demographic, clinical, symptom, and psychosocial adjustment characteristics on the initial (preoperative) levels of FCR and trajectories of FCR over the six months following surgery. Methods Prior to and for six months following breas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
75
2
4

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 68 publications
(90 citation statements)
references
References 59 publications
9
75
2
4
Order By: Relevance
“…They are thus more prepared for cooperation with the healthcare providers in the follow-up period, using their knowledge and understanding of the discussed issues [23]. Furthermore, a study evaluating the perceptions and needs of breast cancer survivors in relation to health care, revealed that survivors often had the perception that healthcare providers could not meet their needs [24], which may invoke FCR [25]. Among the strengths of the present study are that all women treated for breast cancer registered in the hospitalbased electronic chart system during a three-month period were asked to participate.…”
Section: Discussionmentioning
confidence: 99%
“…They are thus more prepared for cooperation with the healthcare providers in the follow-up period, using their knowledge and understanding of the discussed issues [23]. Furthermore, a study evaluating the perceptions and needs of breast cancer survivors in relation to health care, revealed that survivors often had the perception that healthcare providers could not meet their needs [24], which may invoke FCR [25]. Among the strengths of the present study are that all women treated for breast cancer registered in the hospitalbased electronic chart system during a three-month period were asked to participate.…”
Section: Discussionmentioning
confidence: 99%
“…20 A substantial proportion of patients who transition to cancer survivor status face lingering fears of recurrence and residual physical and emotional sequelae. 21 Together, diagnosis and treatment of cancer pose a cascade of physical, emotional, practical, and social demands on the individual and their support network.…”
Section: Cancer As a Traumatic Stressormentioning
confidence: 99%
“…In another study, breast cancer patients were assessed prior to surgery and 6 months post-surgery for risk factors associated with higher FOR. 48 Risk factors for higher FOR scores at 6 months after treatment included, paradoxically, living with someone as compared to living alone, as well as greater changes in spiritual life, higher state anxiety, more self-reported difficulty coping, or reported more distress due to family members. The authors recognized that living with a partner may be counterintuitive to higher levels of FOR, but they did posit that if a person has low coping self-efficacy, this person may have difficulty navigating the relationships in the context of cancer.…”
Section: Anxiety and Depression In Different Populations Of Survivorsmentioning
confidence: 99%
“…Other research has defined risk factors as female, less than 60 years of age, 5-7 years post-diagnosis, social isolation, less than 10 years of education, and survivors who had a recurrence. 49 Women who had the greatest declines in their FOR scores over time were those who had better physical health along with higher FOR scores at the time of enrollment 48 . In breast cancer survivors who were getting their mammograms, women who reported greater perceived risk, lower coping self-efficacy and greater reassurance-seeking behaviors were more likely to be in the higher FOR group.…”
Section: Anxiety and Depression In Different Populations Of Survivorsmentioning
confidence: 99%